G407(P) Improving delivery of care in chronic conditions: a pivotal clinical audit of a hospital access scheme for high-risk or chronically ill children. (7th April 2014) - Cyriac, J; Kamhieh, Y; Kundagrami, S; Mukherjee, K; Andrews, J
Abstract : Aims: Most paediatric departments in the United Kingdom have informal systems of identifying long-term patients who need direct access to urgent hospital care. No national standards exist for these schemes. A patient safety incident in our hospital triggered a review of our own 'yellow-card' direct access scheme. Methods: This was a multi-disciplinary retrospective audit of the existing scheme covering notes for N = 267 patients, spanning ten years. Standards were derived from good practice recommendations from senior clinicians and nursing leads in addition to nursing staff who answer patient telephone calls (Table 1 ). Results: Our key findings (Figure 1 ) were that only 29% of cards listed the reason for direct access, 14% indicated severity, 10% contained plans for junior staff, and only 2% specified whether the child required urgent senior review. None of the cards had a date of issue or a date of review. There was no robust system to identify patients in need of yellow cards at discharge from the paediatric or neonatal wards. To address these deficiencies, we recommended upgrading from the current paper-based to an electronic system. The hospital IT department tailored a software system (Figure 2 ) to our recommendations, allowing consultants to generate cards for these high risk patients which could be viewed by nursing and medical staff. Consultants set individual card review dates, which self generate email reminders, and can attach documents pertaining to each condition, including management advice for frontline staff. A traffic-light colour scheme indicates severity of the condition and need for senior review without delay. The system logs frequency and reasons for patient calls, auto-generating audit trails. A reminder was incorporated into the discharge checklist on the paediatric and neonatal wards providing a fail-safe method of identifying vulnerable children in need of future direct access. Conclusions: We feel that that this is a unique audit which demonstrates how a clinical incident brought together staff of all disciplines to collaborate and generate fresh ideas which were translated into a standardised, modern, fail-safe system to improve the quality of care provided to children with complex needs and reduce the risk of future clinical incidents.